Can I protect the wrestlers' spine from long-term damage? - Diezemann, E. D. (International Journal of Wrestling Science, 2019)
I received an email from my colleague, David Curby (Secretary of UWW Scientific Commission) in February 2018 who asked for my reaction to the following: I am involved in a project to improve the neck and back health of wrestlers……….It began with a question from a parent asking: "Is the wrestler`s bridge a safe exercise?" ' A very simple question about an exercise that has been firmly entrenched in the training of wrestlers for centuries, but upon closer investigation, there is not very much information available to provide a definitive answer Hence, this letter requesting your observations and recommendations for the creation and implementation of an age-appropriate program of neck and back strength and flexibility development that is based on science and medicine. Our intent is not to "ban" bridging exercises. The bridge and back arch, though they can be seen as "extreme," are fundamental positions employed in wrestling for both offense and defense. Orthopaedic-traumatological sports medicine is not only based on the knowledge of the shape and function of the musculoskeletal system, but must also deal with the mechanical stresses to the musculoskeletal system caused by the sporting activities.